Relación entre clima social familiar y autoestima en estudiantes de secundaria de una institución educativa del Callao - Robles Agreda, Lucila Asalia (2012)
The present study aimed to establish the relationship between the family social environment and self-esteem in students of an educational institution in the District of Ventanilla - Callao. The research was developed under a descriptive correlational design. The sample was comprised of 150 students between 12 and 16 years. The inventory of self-esteem of Coopersmith (1979) adapted by Ariana Llerena (1995) was applied to the data collection and the scale family Social climate of Moos (1984) adapted by Ruiz and war (1993). The results of this research show low correlation between the family social climate and variable self-esteem. It is concluded that the family social climate that show students in an educational institution in the District of Ventanilla is partially influencing the self-esteem of students.